Recognising realistic emotions and affect in speech: State of the art and lessons learnt from the first challenge - Schuller, Björn; Batliner, Anton; Steidl, Stefan; Seppi, Dino (Speech Communication, 2011)
More than a decade has passed since research on automatic recognition of emotion from speech has become a new eld of research in line with its `big brothers' speech and speaker recognition. This article attempts to provide a short overview on where we are today, how we got there and what this can reveal us on where to go next and how we could arrive there. In a rst part, we address the basic phenomenon reflecting the last fteen years, commenting on databases, modelling and annotation, the unit of analysis and prototypicality. We then shift to automatic processing including discussions on features, classification, robustness, evaluation, and implementation and system integration. From there we go to the first comparative challenge on emotion recognition from speech - the INTERSPEECH 2009 Emotion Challenge, organised by (part of) the authors, including the description of the Challenge's database, Sub-Challenges, participants and their approaches, the winners, and the fusion of results to the actual learnt lessons before we finally address the ever-lasting problems and future promising attempts.
Keywords: emotion; affect; automatic classification; feature types; feature selection; noise robustness; adaptation; standardisation; usability; evaluation